2015
DOI: 10.1371/journal.pntd.0003419
|View full text |Cite
|
Sign up to set email alerts
|

African Adders: Partial Characterization of Snake Venoms from Three Bitis Species of Medical Importance and Their Neutralization by Experimental Equine Antivenoms

Abstract: BackgroundAn alarming number of fatal accidents involving snakes are annually reported in Africa and most of the victims suffer from permanent local tissue damage and chronic disabilities. Envenomation by snakes belonging to the genus Bitis, Viperidae family, are common in Sub-Saharan Africa. The accidents are severe and the victims often have a poor prognosis due to the lack of effective specific therapies. In this study we have biochemically characterized venoms from three different species of Bitis, i.e., B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
2
13
0
1
Order By: Relevance
“…annulifera venom proteins. These carbohydrate residues were found in the venom proteins of different genera of snakes [46, 68, 69, 70], including in important toxic components, such as SVSP and SVMP [69, 70]. Although we have not identified the families of these glycosylated components, it is possible that some of them are linked to SVMPs or SVSPs, as they have predicted molecular masses similar to some of the previously described glycosylated proteolytic enzymes from viperid venoms [69, 70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…annulifera venom proteins. These carbohydrate residues were found in the venom proteins of different genera of snakes [46, 68, 69, 70], including in important toxic components, such as SVSP and SVMP [69, 70]. Although we have not identified the families of these glycosylated components, it is possible that some of them are linked to SVMPs or SVSPs, as they have predicted molecular masses similar to some of the previously described glycosylated proteolytic enzymes from viperid venoms [69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…After the transfer, the membranes were blocked with 5% BSA in Phosphate Buffered Saline (PBS) (8.1 mM sodium phosphate, 1.5 mM potassium phosphate, 137 mM sodium chloride and 2.7 potassium chloride, p.H. 7.2) and then incubated with peroxidase labeled lectins, ConA (1:1000 dilution) or WGA (1:2000 dilution) to detect residues of Mannose and N-acetylglucosamine [46]. Glycosylated proteins were detected using a solution that contained 0.1% hydrogen peroxide plus 0.5 mg/mL DAB.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts to understand how purified venom toxins act are an essential step for changing the current scenario, as new information appears promising for improving treatment. Given this need, the present study aimed to accomplish the purification and partial in vitro characterization of a serine protease from the B. arietans venom, since this venom presented serine protease activity, according to previous proteomic [ 3 ] and functional [ 50 ] studies. In addition, based on the hemorrhaging and hypotension presented by the victims of envenomation, fibrinogen and a peptide homologous to human kininogen were employed for the preliminary biochemical characterization of this SVSP, denominated herein as Kn-Ba.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Kn-Ba, a serine protease with kinin-releasing and human fibrinogen-cleaving activities, was purified to homogeneity from the B. arietans venom through two steps of molecular exclusion chromatography. It is important to clarify that the metalloprotease activity present in the B. arietans venom is also capable of degrading the α and β chains of fibrinogen [ 50 ], and that based on this property we named this serine protease as Kn-Ba, because kinin-releasing activity is mainly attributed to serineproteases.…”
Section: Discussionmentioning
confidence: 99%
“…The envenomation by Bitis often results in severe local damage, hypotension, coagulopathy, thrombocytopenia, and spontaneous local bleeding and, in the absence of antivenom therapy, the accident can be fatal. Bitis arietans is one of the three species of snakes of medical importance in Africa and its venom is considered the most toxic venom of the viper group [ 169 ]. Regarding the plants with inhibitory action upon Bitis snakes, only one in vivo study of antiophidic activity was found until date.…”
Section: Antivenom Activities Of Extracts Of Medicinal Plants Agaimentioning
confidence: 99%